(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
How should scientific evidence – or rather, a scientific hypothesis – be treated by the judge (or juror) who deals with it? Without dwelling on how this type of evidence enters the trial, the paper will expand on the judicial evaluation of scien-tific evidence. The Author retains that the ‘reinforced reasoning’ approach (a decision method structured by necessary steps, made up of arguments concerning salient as-pects of the case under examination and which must be appreciated in order to de-cide) is also applicable in this matter.